Penguatan Literasi Digital dan Inovasi Sosial: Mendorong Kemandirian Era Society 5.0 pada Gampong Alue Dua, Kecamatan Nisam Antara - Zulfikar; Amrullah; Rahmat; Hendiyani, Dina; Fauzi; Nuriman (Jurnal Solusi Masyarakat (JSM), 2025)
The Society 5.0 era marks a shift in community development by integrating advanced technology with human-centered values. This article explores strategic efforts to enhance digital literacy and social innovation as core pillars to foster self-reliance in remote villages. Using a qualitative approach through literature reviews and reflections on community service practices, the study identifies key challenges such as digital infrastructure gaps, limited access to education, and cultural barriers. At the same time, it highlights the untapped local potentials that can be harnessed through digital empowerment. The discussion emphasizes the importance of multi-stakeholder collaboration involving academics, government institutions, and local communities to realize inclusive digital transformation. Findings suggest that integrating technological skills with local knowledge systems not only supports digital inclusion but also stimulates innovation tailored to local needs. In conclusion, the synergy between digital literacy and social innovation emerges as a sustainable strategy to accelerate rural self-sufficiency in the age of Society 5.0, offering a human-centered approach to technological advancement.